Plant-based burger patties are a source of bioaccessible iron and zinc - Jonas Pospiech; Johanita Kruger; Jan Frank (NFS Journal)
Background: The consumption of plant-based meat alternatives has increased substantially in recent years. However, due to the presence of absorption inhibitors, such as phytate, oxalate, and condensed tannins, the uptake of zinc and iron from plant foods may be low. We therefore quantified minerals (Fe, Zn), inhibitors (phytate, oxalate, condensed tannins), and enhancers (ascorbic acid, carotenoids) of mineral absorption in pea protein-, soy protein-, soy flour-, and sunflower protein-based burger patties and the resulting bioaccessibility of the contained iron and zinc conducting in vitro digestion experiments. Results: The soy flour-based burger had nearly complete bioaccessibility for zinc (105 ± 6 %) and iron (101 ± 11 %), while the three other plant burgers had significantly lower bioaccessibilities (zinc, 9–12 %; iron, 43–57 %). The phytate but not the oxalate and condensed tannin contents of the patties were negatively correlated with the bioaccessibility of iron and zinc (p < 0.05). Conclusion: Plant-based meat alternatives may be an important source of bioaccessible iron and zinc, if they contain low amounts of phytate, and may contribute to an adequate supply of these minerals.